Teachers contribution to give the social values of the ninth grade students - El-Ghadi, Hanan Solih; Kamarulzaman Abdul Ghani; Mohd Aderi Che Noh (http://www.ukm.my/jiae/Default.aspx, 2012)
The study aims to find out the extent to which the teacher in giving social values ??of ninth grade students of basic education in Tripoli, and the study relied on the descriptive and analytical tools to analyze the content and form of a questionnaire and scale of social values??, as well as the study relied on curriculum qualitative through the use of the interview, and reached the study sample of teachers (383), and reached a sample of ninth grade students (693) students, and the study found the following results: The results of scale social values ??of ninth grade students that the percentage of social values ??in ninth grade students were high, and had arranged to have as follows: Value meet -social relationships with others - friendship - responsibility - to help - social solidarity, as well as the case for the axis of the contribution of teachers in giving students the social values ??in the area (family, school and community), the results showed that the teacher has contributed to the development of social values ??among the students of ninth grade moderately in social values ??in the area of the family, and contributed to a high degree in the field of community and school.